2012
DOI: 10.1111/j.1753-1411.2011.00059.x
|View full text |Cite
|
Sign up to set email alerts
|

Socio‐Economic Factors and Mental Health of Young People in India and China: An Elusive Link with Globalization

Abstract: Globalization and its related social, cultural, and economic changes have significant mental health outcomes for young people. However, mental health disorders among youth are seldom included in the range of problems linked to globalization. It is imperative that these multifaceted associations are considered in light of the substantial and increasing burden of disease caused by mental illness, particularly in Asian countries, which are comparatively young and in next few decades will be the major sources of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 70 publications
0
12
0
Order By: Relevance
“…[21] This proposition suggests that Depression and Anxiety evidence for higher urban rates of anxiety and MDD [45] while in contrast there appears a more consistent correlation between urban living and rural-urban migration and sub-threshold symptomatology such as stress reactions and psychological distress. [21] This proposition suggests that Depression and Anxiety evidence for higher urban rates of anxiety and MDD [45] while in contrast there appears a more consistent correlation between urban living and rural-urban migration and sub-threshold symptomatology such as stress reactions and psychological distress.…”
Section: Prevalence Of Common Mental Disordersmentioning
confidence: 99%
See 3 more Smart Citations
“…[21] This proposition suggests that Depression and Anxiety evidence for higher urban rates of anxiety and MDD [45] while in contrast there appears a more consistent correlation between urban living and rural-urban migration and sub-threshold symptomatology such as stress reactions and psychological distress. [21] This proposition suggests that Depression and Anxiety evidence for higher urban rates of anxiety and MDD [45] while in contrast there appears a more consistent correlation between urban living and rural-urban migration and sub-threshold symptomatology such as stress reactions and psychological distress.…”
Section: Prevalence Of Common Mental Disordersmentioning
confidence: 99%
“…It has been hypothesized that common mental disorders may be increasing due to psychosocial stressors such as rising urbanization, which has been linked to mental health problems through higher rates of social and income inequality, occupational stress, and unemployment. [21] This proposition suggests that Depression and Anxiety evidence for higher urban rates of anxiety and MDD [45] while in contrast there appears a more consistent correlation between urban living and rural-urban migration and sub-threshold symptomatology such as stress reactions and psychological distress. [46,47] Another explanation for the lack of increase in prevalence over time may be that, while some risk factors for mental disorders have increased (e.g., relationship breakdowns) others have been mitigated to some degree, such as improved living standards leading to, for instance, higher rates of education [48] and lower levels of illness due to communicable disease and malnutrition.…”
Section: Prevalence Of Common Mental Disordersmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings of previous studies show that neighbourhood socio-economic characteristics and deprivation level can have negative effects on development of children and adolescents and have been specifically associated with diverse issues such as delinquency, teen pregnancy, children's behavioural problems, health, health behaviours, mental health and aggression (Bhat & Rather, 2012;Cushon, Vu, Janzen, & Muhajarine, 2011;Drukker et al, 2003;Roosa et al, 2005;Sellstrőm & Bremberg, 2006;Viner et al, 2012). Several empirical studies have demonstrated that the poverty level in a neighbourhood can be associated with children's overall development, as well as that those children from families residing in deprived neighbourhoods exhibit more frequent problem behaviours and show a greater incidence of injury risk and severe bodily harm (Drukker et al, 2003;Haynes, Reading, & Gale, 2003;Kalff et al, 2001;Reading, Langford, Haynes, & Lovett, 1999).…”
Section: Introductionmentioning
confidence: 98%